2016
DOI: 10.1016/j.ijnurstu.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a mindfulness-based intervention on oncology nurses’ burnout and compassion fatigue symptoms: A non-randomized study

Abstract: This study provides preliminary evidence that mindfulness-based interventions may be efficacious in reducing oncology nurses' psychological symptoms and improving their overall well-being, and thus may be worthy of further study in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
201
1
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(225 citation statements)
references
References 56 publications
11
201
1
12
Order By: Relevance
“…In addition to its focus on attention regulation, mindfulness encompasses an orientation towards experience characterized by an attitude of curiosity and acceptance [21]. Prior studies have supported the effectiveness of mindfulness-based interventions in reducing occupational stress, burnout, anxiety and depression, as well as in improving self-compassion and the spiritual well-being of caregivers [2226]. According to a qualitative study conducted recently, palliative care practitioners recognize mindfulness as an important tool to enhance work sustainability [27].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its focus on attention regulation, mindfulness encompasses an orientation towards experience characterized by an attitude of curiosity and acceptance [21]. Prior studies have supported the effectiveness of mindfulness-based interventions in reducing occupational stress, burnout, anxiety and depression, as well as in improving self-compassion and the spiritual well-being of caregivers [2226]. According to a qualitative study conducted recently, palliative care practitioners recognize mindfulness as an important tool to enhance work sustainability [27].…”
Section: Introductionmentioning
confidence: 99%
“…The nine selected studies had similar objectives—the application of mindfulness therapies in health professionals; some focused on attempts to reduce stress levels (Shapiro et al ; Wang et al ), others to improve self‐compassion and mindfulness (Aranda‐Auserón et al ; Franco‐Justo ; Gracia‐Gonzalo et al ), and others to reduce burnout and exhaustion, manage stress, and increase empathy and well‐being by developing mindfulness (Cohen‐Katz et al ; Duarte & Pinto‐Gouveia. ; Martín‐Asuero et al ; Verweij et al ). Table describes the main characteristics of the participants and the selected interventions.…”
Section: Resultsmentioning
confidence: 99%
“…The studies used a controlled experimental design; four articles were randomized (Aranda‐Auserón et al ; Cohen‐Katz et al ; Martín‐Asuero et al ; Shapiro et al ), and five were non‐randomized (Duarte & Pinto‐Gouveia. ; Franco‐Justo ; Gracia‐Gonzalo et al ; Verweij et al ; Wang et al ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tang, Au, Schwarzer, and Schmitz (2001)found in the study on Hong Kong teachers that job burnout would lead to negative mental health; The results showed that the level of physical and mental health of employees with job burnout is lower than that of employees without job burnout (Peterson et al,2008); The results of study by Chen and Kao (2013)show that there is a significant positive correlation between job burnout and health problems and abnormal behavior; the results of study by Laschinger, Borgogni, Consiglio, and Read (2015)show that burnout of newly recruited nurses is positively related to poor mental health; Duarte,and Pinto-Gouveia (2016) agree with the opinion that pressure and burnout of health care professionals are related to several physical and mental health problems.…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%